Study of correlations between filtration and capacitance characteristics of carbonate reservoirs with complex void structure - Inna N. Ponomareva; Vladimir A. Novikov; Dmitriy A. Martyushev; Alexandr V. Raznitsyn (Georesursy, 2024)
The present paper is devoted to the study of geological peculiarities of carbonate productive formations of oil fields and identification of correlations between filtration and capacitive properties of reservoirs with complex structure of void space. The dependence of reservoir permeability on its porosity, called petrophysical, is used in solving a wide range of problems, including geological and hydrodynamic modeling. Carbonate reservoirs have a complex void structure, which causes ambiguous petrophysical dependence and, consequently, insufficient reliability of calculations based on their application. Thus, with respect to the reservoir considered in this article, the standard petrophysical dependence is constructed differentially for pore and fracture type of reservoir voidness and is characterized by the values of the determination coefficient R2=0,81 and R2=0,16, respectively. An extended set of laboratory studies of carbonate core samples from one of the fields of the Perm region, including nuclear magnetic resonance, scanning electron microscopy, and X-ray computed tomography, allowed us to develop new dependencies that are valid for all types of voids and more closely link the filtration and capacitive characteristics of the reservoir (the coefficient of determination R2 exceeds 0,92). The feasibility of using the developed equations was confirmed by conducting a computational experiment using a geological and hydrodynamic model of the considered reservoir. Replacement of the standard petrophysical dependence with the dependences obtained in the article allowed to improve the prognostic ability of the model for both differential and integral development indicators (annual and cumulative oil production, respectively). The results of the study and the applied approaches can be used in solving the problems of designing and modeling the development of carbonate reservoirs to improve the quality of adaptation of historical data in geologic-hydrodynamic models, as well as increasing the degree of reliability of the performed calculations due to a more detailed consideration of the features of the structure of the void space of the rock relative to traditional methods.